2003
DOI: 10.1051/0004-6361:20030042
|View full text |Cite
|
Sign up to set email alerts
|

Temperature determination via STJ optical spectroscopy

Abstract: Abstract. ESA's Superconducting Tunnel Junction (STJ) optical photon-counting camera (S-Cam2) incorporates an array of pixels with intrinsic energy sensitivity. Using the spectral fitting technique common in X-ray astronomy, we fit black bodies to nine stellar spectra, ranging from cool flare stars to hot white dwarfs. The measured temperatures are consistent with literature values at the expected level of accuracy based on the predicted gain stability of the instrument. Having also demonstrated that systemati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The real advantages of superconducting detectors for optical astronomy are energy resolution (R = E/∆E ≈ 50), read noise free output, microsecond timing, and an incredibly large simultaneous wavelength sensitivity -potentially 0.1-6 microns from space (though their quantum efficiency decreases in the infrared as the absorbing metal films become more reflective). They will excel in observations of rare, extremely faint sources where every photon matters [50,51], and for objects showing fast time variability, like pulsars [52,53,54,55], magnetic white dwarfs [56], cataclysmic variables [57], and low-mass X-ray binaries (LMXBs). Figure 1.6 show the kind of combined spectral and timing data that make these devices so interesting.…”
Section: Opticalmentioning
confidence: 99%
“…The real advantages of superconducting detectors for optical astronomy are energy resolution (R = E/∆E ≈ 50), read noise free output, microsecond timing, and an incredibly large simultaneous wavelength sensitivity -potentially 0.1-6 microns from space (though their quantum efficiency decreases in the infrared as the absorbing metal films become more reflective). They will excel in observations of rare, extremely faint sources where every photon matters [50,51], and for objects showing fast time variability, like pulsars [52,53,54,55], magnetic white dwarfs [56], cataclysmic variables [57], and low-mass X-ray binaries (LMXBs). Figure 1.6 show the kind of combined spectral and timing data that make these devices so interesting.…”
Section: Opticalmentioning
confidence: 99%
“…The resulting data can be analysed in terms of energy (colour) bands and their associated ratios (Perryman et al 2001) or even direct spectral fitting (de Bruijne et al 2002;Reynolds et al 2003). In this paper we extend this spectralfitting to accommodate the presence of emission lines, a particularly useful technique for cataclysmic variables due to the swiftness of the eclipse transitions.…”
Section: Spectral Propertiesmentioning
confidence: 99%
“…Precise timing of the Crab-pulsar light curve has shown that the optical pulses have a lead on the radio pulses by 273 ± 65 μs (Perryman et al 1999;Oosterbroek et al 2006). The spectral information provided by the STJs has made possible the direct determination of quasar redshifts (de Bruijne et al 2002b) and stellar temperatures (Reynolds et al 2003). The next step is to increase the field of view further with the use of DROIDs.…”
Section: Introductionmentioning
confidence: 99%